Karyotype evolution in Ronderosia grasshoppers (Orthoptera: Acrididae) - Castillo, Elio Rodrigo D.; Scattolini, M. Celeste; Palacios-Gimenez, Octavio M.; Martí, Dardo A.; Cabral-De-Mello, Diogo C. [UNESP]; Cigliano, María M. (Oxford University Press (OUP), 2023)
Grasshoppers in the genus Ronderosia (divergence time < 5 Mya) provide a special opportunity to examine the impact of chromosome rearrangements (CRs) in evolution and speciation, because they exhibit extensively rearranged karyotypes involving autosome-autosome and autosome-X chromosomes, the latter leading to the formation of a neo-sex chromosome system (neo-SCS). Despite the potential role of CRs in speciation, the general patterns of karyotype changes resulting from CRs in Ronderosia are still unclear. Here we investigated karyotype evolution in eight Ronderosia species using cytogenetic and phylogenetic models of ancestral character reconstruction. The overall findings suggest a central role for CRs in generating variability in chromosome number and neo-SCS across Ronderosia grasshoppers. It also suggests that incipient species with little morphological change, such as those observed in Ronderosia species, could accumulate marked differences in their karyotypes contributing to post-zygotic reproductive isolation. Besides the evolution of chromosome number in the phylogeny of the genus, chromosome change due to centric fusion is coupled with the divergence pattern observed in the group. While a cladogenetic event could represent a case where karyotypic differences result in speciation, further in-depth genomic studies are needed to better understand how these dramatic restructurings of karyotypes may have occurred.
Keywords: neo-sex chromosome; rearrangement; speciation